Ecosystem health assessment in coastal waters by considering spatio-temporal variations with intense anthropogenic disturbance. (October 2017) - Zhang, Feng; Sun, Xiaoxiao; Zhou, Yan; Zhao, Congjiao; Du, Zhenhong; Liu, RenYi
Abstract: In this research, factors that influence ecosystem health assessment (EHA) in coastal waters were grouped into three categories: natural causes, direct human causes, and indirect human causes. Statistical analysis based on previous researches was utilized to determine EHA indicators of the first two categories. For the third category, spatio-temporal patterns of potential EHA indicators are prevalent due to the variations of anthropogenic activities in their spatial and temporal distribution across seascape and over timescales. Various Geographic Information System (GIS) analysis methods were hence incorporated to translate and visualize anthropogenic activities into ecosystem-specific impacts. The most adequate indexes were identified to establish a holistic EHA framework. Case study in the northern coastal waters of Zhejiang Province from 2005 to 2014 excellently highlighted ecosystem health changes over the years and revealed the advantage of visualization efficiency and the superiority of considering intense human disturbance of our EHA method over traditional ones. Highlights: Various GIS methods were incorporated into the selection of Ecosystem Heath Assessment (EHA) indicators. A holistic EHA model was established by considering spatio-temporal variations. EHA results from 2005 to 2014 were visualized and analyzed. The method effectively translated anthropogenic actions into ecosystem-specific impacts. The method is more effective than traditional methods.